Butterfly Gardening : The North American Butterfly Association Guide - Hurwitz, Jane (Princeton University Press, 2018)
An indispensable and lavishly illustrated guide to creating a garden that attracts and sustains butterfliesButterfly gardening creates habitats that support butterflies, connecting us with some of the most beautiful creatures in the natural world and bringing new levels of excitement and joy to gardening. In this engaging and accessible guide, lavishly illustrated with more than two hundred color photographs and maps, accomplished butterfly gardener Jane Hurwitz presents essential information on how to choose and cultivate plants that will attract a range of butterflies to your garden and help sustain all the stages of their life cycles. An indispensable resource for aspiring and experienced butterfly gardeners alike, Butterfly Gardening is the most gardener-friendly source on the subject, covering all the practical details needed to create a vibrant garden habitat that fosters butterflies. It tells you which plants support which butterflies, depending on where you live; it describes what different butterflies require in the garden over the course of their lives; and it shows you how to become a butterfly watcher as well as a butterfly gardener.While predominantly recommending regionally native plants, the book includes information on non-native plants. It also features informative interviews with experienced butterfly gardeners from across the United States. These gardeners share a wealth of information on plants and practices to draw butterflies to all kinds of gardens--from small suburban gardens to community plots and larger expanses.Whether you are a gardener who wants to see more butterflies in your garden, a butterfly enthusiast who wants to bring that passion to the garden, or someone who simply wants to make their garden or yard friendlier to Monarchs or other butterflies, this is a must-have guide.An essential guide for aspiring and experienced butterfly gardenersEncourages readers to rethink gardening choices to support butterflies and other pollinators in their gardens and communitiesIntroduces gardeners to butterfly watchingIncludes regional lists of plant species that are time-proven to help sustain butterflies and their caterpillarsFeatures informative interviews with expert butterfly gardeners from across the United States